Pengaruh Latihan Shooting Menggunakan Punggung Kaki dan Kaki Bagian dalam Terhadap Kemampuan Shooting dalam Permainan Futsal di SD Inpres 7/83 Poleonro - Alihzan, Dedi; Darminto, Andi Ogo; Rijaluddin, Khalid; Songe, Andi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
Based on the formulation of the problem above, this study aims to determine the effect of Shooting Practice Using the Instep and Inside of the Foot on Shooting Ability in Futsal Games at SD Inpre 7/83 Poleonro. This study uses quantitative research with an experimental design, the two-group pretest-posttest design. The location of the study is at SD Inpres 7/83 Poleonro. The population of this study were all male students at SD Inpres 7/83 Poleonro while the sample of this study was some male students at SD Inpres 7/83 Poleonro. The variables in this study used two variables, namely the independent variable is the shooting practice method using the instep and the shooting practice method using the inside of the foot and the dependent variable is the ability to shoot. The research instrument was a test using a pretest and posttest. Data analysis used a normality test, a homogeneity test and a hypothesis test using the SPSS 26 program.